2011
DOI: 10.1007/s11162-010-9209-9
|View full text |Cite
|
Sign up to set email alerts
|

Are the Effects of Student–Faculty Interaction Dependent on Academic Major? An Examination Using Multilevel Modeling

Abstract: Using multilevel models, this study examined whether and why the strength of association between student-faculty interaction and student cognitive skills development varies across academic majors. The study utilized data from the 2008 University of California Undergraduate Experience Survey (UCUES) and a sample of 43,014 students from 119 academic majors across nine campuses. The results indicate that the impact of interaction with faculty on students' cognitive skills development significantly varies by acade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 40 publications
5
34
0
1
Order By: Relevance
“…For example, in a study by Pascarella et al (1996), higher education was found to have a positive and increasing (i.e., throughout an academic year) impact on the quality of CT of students pursuing a two or four-year undergraduate degree, regardless of academic major. Then, there is research showing that cognitive skills do indeed develop differently according to academic major; for example, Kim and Sax (2011) indicate that the development of cognitive skills is less evident in the fields of the social sciences/humanities. However, this association was mediated by a positive impact of student-teacher interaction: students in academic majors characterized by positive communication and supportive interaction with teachers, and a well-structured program that highlights skills related to CT, were the ones who showed higher gains in the development of their thinking skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in a study by Pascarella et al (1996), higher education was found to have a positive and increasing (i.e., throughout an academic year) impact on the quality of CT of students pursuing a two or four-year undergraduate degree, regardless of academic major. Then, there is research showing that cognitive skills do indeed develop differently according to academic major; for example, Kim and Sax (2011) indicate that the development of cognitive skills is less evident in the fields of the social sciences/humanities. However, this association was mediated by a positive impact of student-teacher interaction: students in academic majors characterized by positive communication and supportive interaction with teachers, and a well-structured program that highlights skills related to CT, were the ones who showed higher gains in the development of their thinking skills.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors claim that cognitive skills develop differently according to academic major (Kim & Sax, 2011); others state that what is determinant for the development of CT is the teacher's approach (Brint, Cantwell, & Saxena, 2012), or well-structured classroom instruction that fosters a more active, participative, and reflexive approach to learning from students (Pascarella, Wang, Trolian, & Blaich, 2013). As for the association between CT and gender, CT may not be directly dependent on gender , perhaps due to its strong situational nature, making it influenced by, and adapted to, contextual settings.…”
Section: Critical Thinking and Real-world Outcomesmentioning
confidence: 99%
“…Thus, cognitive development in the academic major is an important avenue of research. In a large study of student-faculty interaction, utilizing data from forty-three thousand students studying in one hundred and nineteen different academic majors at nine colleges and universities, student-faculty interaction did not impact students uniformly across disciplines (Kim & Sax, 2011). The study determined that the level of cognitive skill development of college students that results from interacting in meaningful ways with faculty varied by academic major, including the fact that the departmental climate also played a role (Kim & Sax, 2011).…”
Section: Cognitive Development In the Classroommentioning
confidence: 98%
“…In a large study of student-faculty interaction, utilizing data from forty-three thousand students studying in one hundred and nineteen different academic majors at nine colleges and universities, student-faculty interaction did not impact students uniformly across disciplines (Kim & Sax, 2011). The study determined that the level of cognitive skill development of college students that results from interacting in meaningful ways with faculty varied by academic major, including the fact that the departmental climate also played a role (Kim & Sax, 2011). While both general student-faculty interaction, and working on research with faculty did generally positively impact cognitive development of college students, research engagement had a higher impact on cognitive development, and this was true for students from diverse backgrounds as well (Kim & Sax, 2011).…”
Section: Cognitive Development In the Classroommentioning
confidence: 99%
See 1 more Smart Citation